In vivo evaluation of cp Ti implants with modified surfaces by laser beam with and without hydroxyapatite chemical deposition and without and with thermal treatment: topographic characterization and histomorphometric analysis in rabbits - Queiroz, Thallita Pereira; de Molon, Rafael Scaf [UNESP]; Souza, Francisley Ávila [UNESP]; Margonar, Rogério; Thomazini, Anahi Herrera Aparecida [UNESP]; Guastaldi, Antônio Carlos [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (Springer Nature, 2017)
Objective: We aimed to assess the surfaces of commercially pure titanium implants (cp Ti) with modified surfaces by laser beam (LS) with and without hydroxyapatite (HA) deposition, without (HAB) and with (HABT) thermal treatment. Furthermore, we have compared them with implants with surfaces modified by acid treatment (AS) and with machined surfaces (MS) utilizing histomorphometric and descriptive histologic analyses. Material and methods: Surface topography characterization was analyzed by scanning electron microscopy (SEM), X-ray energy-dispersive spectroscopy (EDX), and surface roughness (Ra) before implant installation. Forty-five rabbits received seventy-five implants in their left and right tibias and were randomly divided into five groups (n = 5 implants per group): (1) cp Ti implant modified by LS, (2) cp Ti implant modified by laser beam associated with HA deposition without heat treatment (HAB), (3) cp Ti implant modified by laser beam associated with HA deposition with heat treatment (HABT), (4) cp Ti implant with modified surface by means of acid treatment (Master Porous) commercially available (AS), and (5) cp Ti implant with MS commercially available. After 30, 60, and 90 days, the animals were euthanized and the implants and surrounding bone were removed and prepared by a non-decalcified histological process. The percentage of bone-to-implant contact (BIC) and the bone area fraction occupancy (BAFO) between the first three threads was evaluated to the higher cortical region. Results: BIC (%) was statistically superior (p < 0.001) on the LS (69.36 ± 7.91, 71.67 ± 8.79, and 79.69 ± 3.3), HAB (73.22 ± 3.75, 69.48 ± 1.89, and 75.7 ± 4.62), and HABT (65.41 ± 5.51, 71.3 ± 2.5, and 79.68 ± 5.01) compared with AS (49.15 ± 5.76, 41.94 ± 2.85, and 57.18 ± 7.81) and MS (36.69 ± 7.24, 52.52 ± 2.75, and 51.31 ± 6.96) in the 30, 60, and 90-day periods, respectively. BAFO (%) of HAB at 30 days (90.17 ± 6.24) was statistically superior (p < 0.01) to all the other groups. At 60 and 90 days, BAFO of LS (87.17 ± 5.9 and 87.99 ± 2.52), HAB (85.95 ± 3.93 and 82.17 ± 3.65), and HABT (83.27 ± 1.44 and 88.67 ± 2.67) was higher than the AS (77.49 ± 5.83 and 76.42 ± 5.98) and MS (74.01 ± 4.68 and 73.81 ± 4.91). Conclusions: Collectively, our data indicate that the modified surfaces LS, HAB, and HABT favored the interaction between bone and implant and increased bone formation. In addition, HAB showed higher biological behavior favoring the osseointegration. Clinical relevance: Our study provides evidence that LS, HAB, and HABT-modified surfaces improved bone-to-implant contact and increased bone formation around osseointegrated implants compared to conventional machined implants favoring the osseointegration process.
Keywords: Dental implantation; Histomorphometric analysis; Hydroxyapatite; Laser; Surface properties